Sensor fault detection algorithm based on credibility and neighbor-cooperation - Yan-fei LIN; Su-jie SHAO; Cheng ZHONG; Shao-yong GUO; Xue-song QIU (Tongxin xuebao)
To effectively detect whether a node was failure,one of the effective sensor fault detection methods was to compare historical data of suspicious node with its neighbors.The key points of this method were identification of suspicious nodes,as well as decision problem of sending timing for fault diagnosis messages.To this end,a sensor fault detection algorithm was presented based on credibility and neighbor-cooperation.Firstly,a credibility model to determine whether nodes are suspicious was established.Then suspicious nodes send fault diagnosis requests to neighbor nodes based on neighbor-cooperation.The sending timing was determined by equal probability time window.Finally,it could finish classification of fault condition and state judgment based on diagnosis responds of neighbor nodes.Simulation experiments show that this algorithm can achieve higher fault detection rate with less fault diagnosis times and low data congestion probability.